THE VALUE OF TRANSLATING ARCHAIC AND HISTORICAL WORDS OF UZBEK NOVELS INTO FOREIGN LANGUAGES - I. K. Ablakulova (Modern American Journals, 2025)
This article analyzes the degree of scientific accuracy in the translation of archaic and historical words found in Uzbek novels. Historical vocabulary serves as an important means of expressing national identity, the spirit of the era, and the cultural memory of a people. Therefore, when translating such words into foreign languages—especially English, Russian, and other European languages—it is crucial to convey their semantic precision, connotative meaning, period color, and national spirit. The article discusses the place of archaic and historical lexical units in Uzbek literature, the level of scientific accuracy in their translation, and the challenges of rendering them adequately in another language.
Keywords: Archaic words, historical vocabulary, translation, semantic equivalence, adequacy, national spirit, historical color, lexical transformation